Surveillance on Healthcare Workers During the First Wave of SARS-CoV-2 Pandemic in Italy: The Experience of a Tertiary Care Pediatric Hospital - Guarnieri, Valentina; Moriondo, Maria; Giovannini, Mattia; Lodi, Lorenzo; Ricci, Silvia; Pisano, Laura; Barbacci, Paola; Bini, Costanza; Indolfi, Giuseppe; Zanobini, Alberto; Azzari, Chiara (Frontiers in Public Health, 2021)
Healthcare workers (HCWs) have a central role in handling the ongoing COVID-19 pandemic. Monitoring HCWs, both symptomatic and asymptomatic, through screening programs is critical to avoid the spread of SARS-CoV-2 infection in the hospital setting, to rapidly identify and isolate infected ones and to allow their prompt return to work as soon as recovered. We aim to describe our healthcare surveillance experience (April 2-May 6,2020) based on a combined screening consisting of RT-PCR on nasopharyngeal (NP) swabs and rapid serologic test (RST) for SARS-CoV-2, on all HCWs of Meyer Children’s University Hospital in Florence. Among HCWs analyzed, 13/1690 (0.77%) - all of them without clinical manifestations - were found positive at RT-PCR on NP swab: 8/1472 (0.54%) were found during the screening, 1/188 (0.53%) because the contact of a positive, while 4/30 (13.33%) were found positive on the day of re-admission at work after an influenza-like-illness (p=0.00001 versus screening group). No case occurred among non-patients-facing HCWs (p=0.04 versus patient-facing group). Nurses and residents represented respectively the working role with the highest and lowest percentage of RT-PCR positivity. Concerning working areas, the majority of RT-PCR positivity (12/13) and IgM-IgG positivity (34/42) were found in non-COVID-19 dedicated areas (p=0.08 versus COVID-19 dedicated areas). In conclusion, during the epidemic season, the risk for a worker who recovered from an influenza-like-illness to be still positive and infectious for SARS-CoV-2 is significantly high and suggest that the decision of the hospital to test all workers before re-admission at work may be wise and relevant.